2015
DOI: 10.30958/ajspo.2-2-4
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Influencing Fans’ Attendance at Football Matches in the Kingdom of Saudi Arabia

Abstract: This quantitative study investigates factors that affect fans' attendance at football stadiums to watch Saudi Premier League (SPL) football matches. We adopted the comparative quantitative research method to compare the significance of the factors, which affect fans' attendance at the football stadiums. Data was collected through a questionnaire. The research was carried out on a sample of 1,506 participants. The factors which have the most effect on fans' attendance are the facilities and services offered by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…In this study the findings showing that the majority of the fans (50.8%) have attended the football matches in the stadium while only 23.7% of the total participants in the study stated that their favorite way to watch their team is by attending to the stadiums, this percentage is a huge in relation to a previous study done by Binjwaied et. al, (2015) which stated that only 1.9% of Saudi football fans prefer to watch the matches in the stadiums.…”
Section: Figure (6): Fans Planning To Attend Football Matchessupporting
confidence: 44%
See 2 more Smart Citations
“…In this study the findings showing that the majority of the fans (50.8%) have attended the football matches in the stadium while only 23.7% of the total participants in the study stated that their favorite way to watch their team is by attending to the stadiums, this percentage is a huge in relation to a previous study done by Binjwaied et. al, (2015) which stated that only 1.9% of Saudi football fans prefer to watch the matches in the stadiums.…”
Section: Figure (6): Fans Planning To Attend Football Matchessupporting
confidence: 44%
“…Although another previous study by Plumley and Flint (2015) addressed the imbalance distribution of the clubs in the competition of UEFA champions league and the effect of placing the teams in the groups reflect on the performance in the competition and therefore on their revenues as each team allocate more money prize as they proceed in the competition, in the same paper advised that the fair grouping of the clubs is a must in order to make a fair distribution. Fans are the soul of the football and the factors that influence them to attend the football matches in Saudi Arabia have been investigated in a quantitative study done by Binjwaied et al (2015) as the results showed that the most factors were related to the infrastructure of football facilities and the services at them as their study showed that 55.4% of the participants would never attend a football match in the stadium.…”
Section: Em-2022-3831mentioning
confidence: 99%
See 1 more Smart Citation
“…The economics of football analyze the behavior of consumers (fans) and producers (clubs). Examples of studies focusing on fans/spectators include Abdel-Naby Ibrahim (2014), Binjwaied et al (2015), Borges (2018), Desbordes (2020, 2021), Harasta (2021), Özgen andArgan (2017), andPfeffel et al (2017).…”
Section: A Brief Review Of Selected Football Studiesmentioning
confidence: 99%
“…Similarly, a number of studies have used the various aspects of developing a new trend; that of e-sports-see Robeers and Van Den Bulck (2018), Lemcke and Weh (2018) and Wewer (2018). Binjwaied et al (2015) examine the factors which affect the attendance of football matches in the Kingdom of Saudi Arabia. They conclude that the role of media is important in attracting more fans such as via televised media, online coverage and social media.…”
Section: Introductionmentioning
confidence: 99%